Jared Sparks papers - Sparks, Jared, 1789-1866.
Letters (1825-1865, undated) written by Sparks to Hermanus Bleecker, George W. Cullum, William Gowans, Charles Carter Lee, E. Magrath, William M. Meredith, Nathaniel Niles, Benjamin Silliman, George Corbin Washington, and others; publisher's agent's record book (undated) of subscriptions for Sparks's works; maps of Hudson River fortifications in New York state; and a print from an engraved portrait of Sparks.
In part, positive photocopies and facsimiles.
Editor and author.
Collection material in English.
Forms part of: Miscellaneous Manuscripts collection.
Keywords: Bleecker, Harmanus, -- 1779-1849 -- Correspondence; Cullum, George W. -- 1809-1892 -- Correspondence; Gowans, William, -- 1803-1870 -- Correspondence; Lee, Charles Carter, -- 1798-1871 -- Correspondence; Magrath, E. -- Correspondence; Meredith, William M. -- 1799-1873 -- Correspondence; Niles, Nathaniel, -- 1791-1869 -- Correspondence; Silliman, Benjamin, -- 1779-1864 -- Correspondence; Washington, George Corbin, -- 1789-1854 -- Correspondence; Booksellers and bookselling -- United States -- 19th century; Fortification -- New York (State); Hudson River Valley (N.Y. and N.J.) -- History -- Revolution, 1775-1783.; New York (State) -- History -- Revolution, 1775-1783.; United States -- History -- Revolution, 1775-1783 -- Maps; Authors; Editors